2007
DOI: 10.1007/s10570-007-9192-2
|View full text |Cite
|
Sign up to set email alerts
|

Glass transition temperature and thermal decomposition of cellulose powder

Abstract: Cellulose powder and cellulose pellets obtained by pressing the microcrystalline powder were studied using differential scanning calorimetry (DSC), differential thermal analysis (DTA), and thermal gravimetry (TG). The TG method enabled the assessment of water content in the investigated samples. The glass phase transition in cellulose was studied using the DSC method, both in heating and cooling runs, in a wide temperature range from -100 to 180°C. It is shown that the DSC cooling runs are more suitable for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
158
1
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 280 publications
(188 citation statements)
references
References 8 publications
21
158
1
8
Order By: Relevance
“…However, the shift in the glass transition temperature of the wet resin system shows a confinement effect as discussed by Arndt et al 47 for salol relaxation dynamics in nanometer size pores; the relaxation rate of the confined material increased compared to bulk material. Some other examples of observed low T g with moisture/ water content can be found in the literature, 10,11,48 where change in the glass temperature was reported for inulin, epoxy resins and cellulose. The epoxy system studied 11 showed that the glass transition estimated from the mechanical modulus shifted to lower temperatures with different moisture treatment with shift related to the moisture weight gain, which we have not included in this work.…”
Section: Dielectric Relaxation Mapmentioning
confidence: 84%
See 2 more Smart Citations
“…However, the shift in the glass transition temperature of the wet resin system shows a confinement effect as discussed by Arndt et al 47 for salol relaxation dynamics in nanometer size pores; the relaxation rate of the confined material increased compared to bulk material. Some other examples of observed low T g with moisture/ water content can be found in the literature, 10,11,48 where change in the glass temperature was reported for inulin, epoxy resins and cellulose. The epoxy system studied 11 showed that the glass transition estimated from the mechanical modulus shifted to lower temperatures with different moisture treatment with shift related to the moisture weight gain, which we have not included in this work.…”
Section: Dielectric Relaxation Mapmentioning
confidence: 84%
“…6 The presence of water and its influence in the dielectric response were previously studied in various polymeric systems. [7][8][9][10][11] Here, we concentrate on the change in the dielectric properties of highly filled composites in the presence of water, and report on the dielectric relaxation of moisture-absorbed and dry samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal stability has been characterized by thermogravimetry analysis (TGA) [10] and physical structure by differential scanning calorimetry (DSC) [11]. In the literature, thermogravimetry analyses of cellulose point out two weight losses; the first one in the range of 40 to 80°C attributed to the water evaporation [11][12][13] and the second one in the temperature range of 200 to 400°C, to polymer degradation.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, thermogravimetry analyses of cellulose point out two weight losses; the first one in the range of 40 to 80°C attributed to the water evaporation [11][12][13] and the second one in the temperature range of 200 to 400°C, to polymer degradation. During this decomposition, the principal products are water and carbon dioxide [5,11,12,14,15].…”
Section: Introductionmentioning
confidence: 99%